Membangun Etika Pergaulan Remaja melalui Bimbingan Klasikal di SMP Muhammadiyah 6 Samarinda - Marsela Puji Lestari; Isnaini Septian Nur Rochmah; Annisa Nanda Rahmadani; Siti Anisatus Zahrok; Nur Indah; Ziyada Tsaniya; Rudy Hadi Kusuma (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
Adolescence is an important period in the formation of a person's personality, where individuals tend to be easily influenced by the social environment including associations. Unhealthy associations have the potential to cause various problems such as peer pressure, low self-confidence, and the emergence of deviant behavior. This service activity aims to increase the awareness and understanding of Muhammadiyah 6 Samarinda Junior High School students regarding the importance of applying ethics in society through the provision of classical guidance services. The activity, which carries the theme